Fetuin A Concentration in the Second Trimester Amniotic Fluid of Fetuses with Trisomy 21 Appears to Be Lower: Phenotypic Considerations. (6th February 2012) - Iliodromiti, S.; Vrachnis, N.; Samoli, Evangelia; Iliodromiti, Z.; Pangalos, C.; Drakoulis, N.; Creatsas, G.; Botsis, D.
Abstract : Objective . We investigated whether the concentration of the glycoprotein fetuin A is altered in the second trimester amniotic fluid of trisomy 21 pregnancies compared with euploid pregnancies. Methods . 25 pregnancies with an extra chromosome 21 were matched for maternal and gestational age with 25 pregnancies with normal karyotype. Levels of fetuin A in amniotic fluid were measured by a commercially available enzyme-linked immunosorbent assay (ELISA) kit. Results . The median concentration of fetuin A in amniotic fluid of trisomy 21 pregnancies (5.3 ng/ml) was statistically significantly lower (P value = 0.008 ) compared with that in euploid pregnancies (6.8 ng/mL). Conclusion . Lower levels of fetuin A in trisomy 21 may indicate an association with altered metabolic pathways in this early stage that could potentially be associated with features of the syndrome, such as growth restriction or impaired osteogenesis.